Evaluation Of The Myorion Application Implementation In The Accounting Information System Of PT Guna Bangun Jaya Medan - Trisha Debbie Sanora Gultom; An Azzahra Azzahra; Nur Aliah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to evaluate the implementation of the MyOrion application as an Enterprise Resource Planning (ERP)–based accounting information system at PT Guna Bangun Jaya Medan. The evaluation assesses the success of the system in supporting the company’s accounting processes using the DeLone and McLean information systems success model, which consists of system quality, information quality, service quality, system use, user satisfaction, and net benefits. This study employs a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving system users and relevant stakeholders within the company. The findings indicate that the MyOrion application has been implemented effectively and is able to integrate sales, inventory, distribution, and financial recording processes in real time. The system contributes positively to operational efficiency and the accuracy of accounting information. However, several challenges remain, particularly related to users’ understanding of the system and technical stability issues. This study provides evaluative insights and practical implications for improving the effectiveness of ERP-based accounting information systems.